2015
DOI: 10.1007/s12263-015-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrative network-based analysis of mRNA and microRNA expression in 1,25-dihydroxyvitamin D3-treated cancer cells

Abstract: Nutritional systems biology is an evolving research field aimed at understanding nutritional processes at a systems level. It is known that the development of cancer can be influenced by the nutritional status, and the link between vitamin D status and different cancer types is widely investigated. In this study, we performed an integrative network-based analysis using a publicly available data set studying the role of 1,25-dihydroxyvitamin D3 (1,25(OH)2D3) in prostate cancer cells on mRNA and microRNA level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
2
8
1
Order By: Relevance
“…The modulation of miRs by VD is reported here for the first time in the context of obesity-associated comorbidities; similar ability has been widely described in cancer context. Indeed, differential regulation of miR expression profiles by 1,25(OH) 2 D has been demonstrated in prostate cancer cells [40], bladder cancer cells [41], and in lung cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of miRs by VD is reported here for the first time in the context of obesity-associated comorbidities; similar ability has been widely described in cancer context. Indeed, differential regulation of miR expression profiles by 1,25(OH) 2 D has been demonstrated in prostate cancer cells [40], bladder cancer cells [41], and in lung cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…In THP-1 cells only, 1,25(OH) 2 D3 potently regulated genes involved in progression of cell cycle and DNA replication, consistent with the neoplastic origin of these cells. The pathways with high Z-score include retinoblastoma in cancer, G1 to S cell cycle control, DNA replication and cell cycle, are similar to those reported previously for prostate cancer cells treated with 1,25(OH) 2 D3[132]. This suggests that, in addition to its common metabolic innate immune targets, 1,25(OH) 2 D3 also has common antiproliferative targets in neoplastic cell types, including suppression of key proteins that participate in progression of the cell cycle and regulation of DNA replication[129].…”
supporting
confidence: 86%
“…Furthermore, studies in the last two decades have explored the anti-proliferative properties of vitamin D in malignant neoplastic cells [54] [130]. Notably, two studies (one of them discussed in Chapter 4) carried out a similar pathway analysis that described in this thesis and showed that 1,25(OH) 2 D3 represses gene expression of cell cycle components in prostate and myeloid cancer cell lines [132] [81]. Finally, throughout this thesis we will explain in more detail the role of vitamin D in the immune system, showing that its different immunomodulatory roles, depending on immune cell type, have the potential to generate a specific immune response.…”
Section: Metabolism Of Vitamin D and Tissue-specific Actionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kutmon et al uses a publicly available data set of changes in transcript and microRNA abundances in prostate cancer cells treated with 1,25-dihydroxyvitamin D3 (Kutmon et al 2015). PathVisio and Cytoscape network tools identified cell cycle and cancer-specific pathways altered by this vitamin.…”
mentioning
confidence: 99%